Catastrophic famine in Gaza: Unprecedented levels of hunger post-October 7th. A real population-based study from the Gaza Strip - MoezAlIslam Faris; Ayman S. Abutair; Reham M. Elfarra; Nida. A. Barqawi; Amal M. Firwana; Rawan M. Firwana; Madleen M. AbuHajjaj; Shaimaa A. Shamaly; Samar S. AbuSamra; Hanan S. Bashir; Noor A. Abedalrahim; Noor A. Nofal; et al. (PLoS ONE, 2025)
Background The Gaza Strip, spanning approximately 365 square kilometers, has been a focal point of geopolitical tensions and humanitarian crises. The military escalation on October 7th exacerbated existing vulnerabilities, notably food security and hunger, with an estimated 85750 deaths due to Israeli attacks, representing about 8% of the 2.34 million population. This research aims to provide policymakers and humanitarian organizations with actionable insights, such as identifying the most vulnerable populations, quantifying the impact of specific restrictions, and informing the development and implementation of targeted interventions that improve long-term food security and alleviate human suffering in Gaza. Methods A cross-sectional study was conducted from May to July 2024, assessing food insecurity and hunger among Palestinian households across the five governorates of Gaza. The study applied a quantitative research approach, utilized the Household Food Security Survey Module (HFSSM), Household Food Insecurity Access Scale (HFIAS), and Household Hunger Scale (HHS) to measure food insecurity, famine, and hunger. Self-reported anthropometric data and socioeconomic status were also collected. Data were analyzed using SPSS version 29, employing correlation tests, chi-square analysis, and logistic regression. Results A survey of 1209 households across the Gaza Strip revealed a catastrophic humanitarian crisis. More than 54% of households experienced complete house destruction. Food insecurity reached unprecedented levels, with about 98% of households experiencing severe food insecurity, according to the HFIAS, while 100% experienced different levels of food insecurity as per the HFSSM. A staggering 95% of households experienced other sorts of hunger. The war was associated with significant (p < 0.001) weight loss among individuals, with the average weight dropping from 74.8 ± 15.9 kg before the war to 64.8 ± 15.2 kg, concomitant with significant (p < 0.001) reduction in BMI from 26.4 ± 5.4 to 22.8 ± 5.2 kg/m2. Factors such as displacement, age, socioeconomic status, and educational level significantly exacerbated hunger severity. Conclusion The study reveals a severe food insecurity and hunger crisis in the Gaza Strip, exacerbated by the ongoing damaging attacks by Israeli forces. These findings underscore the urgent need for immediate and sustained humanitarian assistance to address the critical food security and nutritional needs of the Gazan population.